2014
DOI: 10.1007/s00438-014-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of apolipoprotein E gene polymorphisms with cerebral palsy in Chinese infants

Abstract: Apolipoprotein E (APOE, protein; ApoE, gene) is a lipid transport protein abundantly present in brain cells. Previous studies have suggested that there is an association between genetic variants of ApoE and susceptibility to cerebral palsy (CP). The purpose of this study was to explore whether the ApoE gene is involved in the etiology of CP in the Chinese population. In this study, 350 CP patients and 242 healthy control children were recruited. Genomic DNA was prepared from venous blood and all five single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Originally hypothesized to be protective, studies have reported a higher rate of the ApoE4 allele among children with CP compared with a community sample, 26 while other studies reported that certain ApoE haplotypes appear protective against CP. 27 Among children with CP, the ApoE4 allele was associated with a worse clinical phenotype in one study, 28 but not confirmed in others. 29,30 An additional study found evidence of risk associated with ApoE alleles E2 and E3.…”
Section: Apoementioning
confidence: 89%
“…Originally hypothesized to be protective, studies have reported a higher rate of the ApoE4 allele among children with CP compared with a community sample, 26 while other studies reported that certain ApoE haplotypes appear protective against CP. 27 Among children with CP, the ApoE4 allele was associated with a worse clinical phenotype in one study, 28 but not confirmed in others. 29,30 An additional study found evidence of risk associated with ApoE alleles E2 and E3.…”
Section: Apoementioning
confidence: 89%
“…Apart from that, haploview software was used for investigating the linkage disequilibrium and the haplotype blocks [25]. SHESIS program was implemented to construct haplotypes and evaluate the relationship between constructed haplotypes and DTC risk [26]. We also assessed multiplicative gene-gene interactions using joint effect models and all significance levels were set at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…In children with CP, clinical observations have been proposed suggesting an unfavorable phenotypic effect regarding the ApoE ԑ4 allele and a protective effect of the ApoE ԑ2 and ԑ3 alleles. 25,26 On the contrary, negative effects of the ԑ4 allele has not been proven with subsequent studies in CP children. 27 In the current study, we aimed to readdress ApoE allelic variants and their role in CP etiology in a small Turkish cohort of CP patients in the light of demographic patient data, perinatal variables, CP-accompanying clinical conditions and neuroimaging findings.…”
mentioning
confidence: 94%